Next-Generation Medical Interventions: The Role of AI, IOT, And Nanotechnology In Enhancing Healthcare Outcomes - Haleem, Asma; David Faijue, Darlington; Magsi, Sohrab Khan; Bangash, Sudhair Abbas (Journal of Neonatal Surgery, 2025)
Background: Next-generation technologies have firmed up their footprints in Healthcare and treatment, including Artificial Intelligence (AI), the Internet of Things (IoT), and nanotechnology. These technologies are helping to improve the diagnosis, patient surveillance, and overall effectiveness of treatments. Nevertheless, costs, data security, and licensable issues remain the barriers to increased popularity. Objective: This research aims to evaluate the effects of the emergence and adoption of AI, IoT, and nanotechnology in healthcare delivery systems and examine the limitations of their optimization. The frequency of use of these technologies and what impacts the adoption of these technologies in the current healthcare systems and patient care is also of interest in the study. Methods: A cross-sectional survey design was used, and participants were recruited through a snowball technique to include only those conversant with these technologies, including healthcare professionals, researchers, and engineers. A sample of 250 respondents completed an online survey using a structured questionnaire. Descriptive, Factor, correlation, and regression analyses were conducted to test for relationships between technology usage and healthcare improvement. Results: The same concluded that the use of AI, IoT, and nanotechnology positively impacts individuals' health. The available literature shows that regular utilization of these technologies relates to improved diagnosis, patient care, and care delivery. Most writers conducted a regression analysis showcasing a positive correlation between the above technologies and general healthcare enhancement. That said, the study also found that there are challenges like high costs of implementing the changes and data privacy and regulation issues. Conclusions: The role of AI, IoT, and nanotechnology can be seen in improving healthcare results by optimizing diagnosis and treatment. However, these technologies bring out the need to understand how to overcome barriers to the same. Efforts to attain these goals through policy adjustments, improved facilities, and the right courses will guarantee that the fruits of these dynamic technologies are not only shared fairly but attained in the first place. Further studies should focus on the issues that may arise in the long run and how they can be prevented from materializing in the long run.